2020
DOI: 10.18330/jwallacea.2020.vol9iss2pp121-132
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stand Damage Due to Timber Harvesting in PT Tunas Timber Lestari, Papua

Abstract: Timber harvesting activities can cause damage to residual stands, this can occur due to improper timber harvesting techniques. The study was conducted at one of PT Tunas Timber Lestari’s IUPHHK-HA in Papua Province. The results showed that: 1). The number of trees felled and skidded on 3 logging compartment with each of the 3 plot of observation sample has an area of 2 ha (the total area of the research is 18 ha) is 16 trees on average; 2). The average number of residual stand (trees with a diameter of ≥ 20 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Root damage was produced only by the chainsaw-skidder system, with 2.4% of damage [33]. Research result by Yuniawati and Dulsalam [34] revealed that the average number of residual stands (trees with a diameter of ≥20 cm) damaged by logging is 26 trees (13.00%) per ha with details of damage to canopy of 4 trees (15.39%), broken branches of 13 trees (50.00%), the trunk wound of 2 trees (7.69%), and the collapsed/tilted of 7 trees (26.92%). Damage to the residual stand in felling is caused more by the lack of skilled chainsaw operators in determining felling direction.…”
Section: Residual Stand Damagementioning
confidence: 99%
“…Root damage was produced only by the chainsaw-skidder system, with 2.4% of damage [33]. Research result by Yuniawati and Dulsalam [34] revealed that the average number of residual stands (trees with a diameter of ≥20 cm) damaged by logging is 26 trees (13.00%) per ha with details of damage to canopy of 4 trees (15.39%), broken branches of 13 trees (50.00%), the trunk wound of 2 trees (7.69%), and the collapsed/tilted of 7 trees (26.92%). Damage to the residual stand in felling is caused more by the lack of skilled chainsaw operators in determining felling direction.…”
Section: Residual Stand Damagementioning
confidence: 99%